Physicochemical Characteristics of Instant Boiled Rice: Study of Sodium Citrate Concentration and Soaking Time - Hawa, La Choviya; Rhomadhona, Widya; Putranto, Angky Wahyu (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Cooked rice (nasi liwet) is a typical rice dish of Java Island which is cooked using spices so that it has a unique taste and aroma. Making nasi liwet takes a long time, so this dish is only served at certain times. Therefore, a fast rice processing technique is needed but still has a distinctive taste and aroma. The purpose of this study is to analyze the physicochemical analysis of instant liwet rice based on the concentration and soaking time of sodium citrate. The physicochemical analysis tested were rehydration time, volume expansion, bulk density, texture, yield, ash content, and water content. The study was conducted by soaking sodium citrate (0, 2, 5, and 8% w/v) and soaking time (2, 4, and 6 hours) on rice. The results showed that the fastest rehydration time for instant nasi liwet was 4.55 minutes. The range of observation parameters such as expansion volume is 66.26-91.24%; bulk density is 0.413-0.581 g/ml; the texture is 431-1496 g/mm; yield is 89.64-92.26%; ash content is 4.11-4.45% and water content is 5.83-7.03%wb. Variations in sodium citrate concentration and immersion time increased the swelling volume and ash content, while water content, bulk density, texture, and yield tended to decrease. The best treatment based on the multiple attribute Zeleny method was immersion of 5% sodium citrate for 4 hours of immersion. Keywords: Immersion Time, Instant Rice, Nasi Liwet, Physicochemical, Sodium Citrate